Peran Biochar-silika dan Pupuk Anorganik Tunggal dalam Meningkatkan Ketersediaan Fosfor dan Hasil Padi Sawah - Muhammad, Fadlan Atalla; Rival, Rival; Citraresmini, Ania; Sofyan, Emma Trinurani; Joy, Benny (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2025)
Rice productivity in Inceptisols is often constrained by high phosphate fixation and low nutrient efficiency, despite high total nutrient reserves. This study aimed to evaluate the effectiveness of silicaenriched biochar in improving soil chemical properties and maintaining rice yield under reduced N, P, K fertilization. A field experiment was arranged in a Randomized Block Design with two factors: silicaenriched biochar (0, 1.25, and 2.5 t ha-1) and N, P, K fertilizer dosages (0, 50%, and 100% of the recommended dose). Observed parameters included Cation Exchange Capacity (CEC), available phosphorus, total soil silica, and yield components. The results showed a significant interaction between treatments on soil chemical properties, particularly CEC and pH. Application of 2.5 t ha-1 silica-enriched biochar independently increased available phosphorus by 24.3% and total soil silica by 5.9% compared to the control, likely due to phosphate desorption mechanisms. Agronomically, while N, P, K fertilizer was the dominant factor for yield, the combination of 2.5 t ha-1 silica-enriched biochar with 50% N, P, K dosage produced Milled Dry Grain (MDG) yields that were statistically comparable to the 100% N, P, K treatment. This indicated that silica-enriched biochar can substitute up to 50% of inorganic fertilizer requirements without compromised yield